The role of visual representation in primary student’s ability to solve fraction word problems - Davina Aurelia; Slamet Arifin; Siti Faizah; Radeni Sukma Indra Dewi; Ratna Ekawati (Beta: Jurnal Tadris Matematika, 2026)
[English]: Difficulties in solving fraction word problems remain a persistent challenge in elementary mathematics education, as students struggle to translate written situations into appropriate mathematical representations and corresponding operations, or vice versa. This study explores how visual representation contributes to primary students’ ability to solve fraction word problems. Despite fractions being fundamental for mathematics advancement, students struggle with translating written problems into mathematical operations. Through a systematic literature review following the PRISMA framework, 28 peer-reviewed articles that were published between 2015 and 2025 were analyzed from Semantic Scholar, ERIC, and Scopus databases using the SPIDER tools for keyword selection. The findings reveal that area models were most frequently used, followed by number lines, bar models, and set models. Furthermore, the findings suggest that visual representations are associated with improved performance in solving fraction word problems and may support students’ conceptual understanding of fractions by organizing information and providing concrete illustrations of abstract concepts. [Bahasa]: Kesulitan dalam menyelesaikan soal cerita pecahan masih menjadi tantangan yang persisten dalam pendidikan matematika tingkat dasar, karena siswa mengalami kesulitan dalam menerjemahkan situasi soal tertulis menjadi representasi matematis yang tepat dan operasi yang sesuai atau sebaliknya. Penelitian ini mengkaji dampak representasi visual terhadap kemampuan siswa sekolah dasar dalam menyelesaikan soal cerita pecahan. Meskipun pecahan merupakan konsep dasar dalam perkembangan matematika, siswa sering kesulitan dalam menerjemahkan soal tertulis menjadi operasi matematika. Melalui tinjauan literatur sistematis berdasarkan kerangka kerja PRISMA, 28 artikel yang diterbitkan antara tahun 2015 dan 2025 dari database Semantic Scholar, ERIC, dan Scopus menggunakan alat SPIDER untuk pemilihan kata kunci. Temuan menunjukkan bahwa model area paling sering digunakan, diikuti oleh garis bilangan, model batang, dan model himpunan; selain itu, temuan tersebut juga mengindikasikan bahwa representasi visual berkaitan dengan peningkatan kemampuan dalam memecahkan soal cerita pecahan dan dapat mendukung pemahaman konseptual siswa tentang pecahan dengan cara mengorganisasikan informasi serta memberikan ilustrasi konkret atas konsep-konsep abstrak.